Isolation and characterization of chromium reducing Vibrio sinaloensis from marine soil - Morshed, Mehmuna (BRAC Univeristy, 2017)
This project report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2016.